Answer:
the initial velocity is 20 m/s and the acceleration is 2 m/s²
Explanation:
Given equation of motion, v = 20 + 2t
If V represents the final velocity of the object, then the initial velocity and acceleration of the object is calculated as follows;
From first kinematic equation;
v = u + at
where;
v is the final velocity
u is the initial velocity
a is the acceleration
t is time of motion
If we compare (v = u + at) to (v = 20 + 2t)
then, u = 20 and
a = 2
Therefore, the initial velocity is 20 m/s and the acceleration is 2 m/s²
1) Length of the wire.
2) Thickness of the wire.
3) Temperature.
4) Type of metal.
Hope this helps!
-Payshence
Answer:
I DONT KNOW WHAT TO DO SORRY
Explanation:
EVEN ME IM NOT SURW
Answer:
a)
Y0 = 0 m
Vy0 = 15 m/s
ay = -9.81 m/s^2
b) 7.71 m
c) 3.06 s
Explanation:
The knowns are that the initial vertical speed (at t = 0 s) is 15 m/s upwards. Also at that time the dolphin is coming out of the water, so its initial position is 0 m. And since we can safely assume this happens in Earth, the acceleration is the acceleration of gravity, which is 9.81 m/s^2 pointing downwards
Y(0) = 0 m
Vy(0) = 15 m/s
ay = -9.81 m/s^2 (negative because it points down)
Since acceleration is constant we can use the equation for uniformly accelerated movement:
Y(t) = Y0 + Vy0 * t + 1/2 * a * t^2
To find the highest point we do the first time derivative (this is the speed:
V(t) = Vy0 + a * t
We equate this to zero
0 = Vy0 + a * t
0 = 15 - 9.81 * t
15 = 9.81 * t
t = 0.654 s
At this time it will have a height of:
Y(0.654) = 0 + 15 * 0.654 - 1/2 * 9.81 * 0.654^2 = 7.71 m
The doplhin jumps and falls back into the water, when it falls again it position will be 0 again. So we can equate the position to zero to find how long it was in the air knowing that it started the jump at t = 0s.
0 = Y0 + Vy0 * t + 1/2 * a * t^2
0 = 0 + 15 * t - 1/2 * 9.81 t^2
0 = 15 * t - 4.9 * t^2
0 = t * (15 - 4.9 * t)
t1 = 0 This is the moment it jumped into the air
0 = 15 - 4.9 * t2
15 = 4.9 * t2
t2 = 3.06 s This is the moment when it falls again.
3.06 - 0 = 3.06 s